Εἶτα and ἔπειτα in Greek Tragedy: From Time Adverbs (Minerva, 2017)
This paper studies εἶτα and ἔπειτα in the tra-gedies of Aeschylus, Sophocles and Euripides preserved complete in order to identify and explain their usages as conjunctive adverbs in contrast to the use as prototypical time adverbs. Eἶτα and ἔπειτα are originally time adverbs pointing out that an event is later than another. However, there are certain documented examples in which they develop discursive usages, organize the statements in the message and express contents related to conjunctions. As conjunctive adverbs, εἶτα and ἔπειτα behave as organizers of the information, additive connectors, counter-argumentative connectors and consecutive connectors. In addition, the studied corpus for this paper also analyses some contexts in which these adverbs are in a state of transition between a purely temporal usage and a discursive usage.
Keywords: times adverbs; conjunctive adverbs; discourse markers; organizers; connectors